DAMPAK SOSIAL BUDAYA MASYARAKAT AKIBAT PANDEMI COVID-19 DI DESA LEILEM KECAMATAN SONDER KABUPATEN MINAHASA - Richard Johanes Bangunang (Universitas Sam Ratulangi, 2022)
The COVID-19 pandemic has brought great changes to all levels of society in various aspects, including socio-cultural aspects. The COVID-19 pandemic has forced restrictions on social activities between individuals from one another, giving rise to habits that are different from previous lives. In other words, this pandemic has given rise to a new culture of society to respond to existing social activity restriction policies. Various social activities that previously we could do freely, now must be done by implementing health protocols. Even for social activities such as weddings, celebrations, thanksgiving, entertainment, worship and so on, it must be stopped. The existence of the policy of Enforcing Restrictions on Community Activities (PPKM). The impact of this pandemic is felt by all parties and circles, anyone cannot deny its existence can only avoid it. The policies of the Central Government and local governments that implement the Implementation of Enforcing Restrictions on Community Activities (PPKM) have increasingly made the social activities in Leilem Village more tenuous, and after PPKM was relaxed, community social activities also remained tenuous due to the community being accustomed to the social life of the community that had been stretched. Keywords: impact, pandemic, social canges